2004 Annual Report on Operations Evaluation. (Newyork; World Bank Group, 2005)
The 2005 Annual Report on Operation Evaluation examines the use of information by World Bank managers to improve development results and enhance the effectiveness of the Bank at the country level. It suggests that greater attention is needed to measure and manage development results at the country level. This will require strengthening countries' performance measurement capacity. The Bank is making progress in strengthening the results focus of its monitoring and evaluation, but more attention is needed to improve performance measurement and tracking progress.
Cover -- Contents -- Acknowledgments -- Foreword -- Acronyms and Abbreviations -- 1 Introduction -- Relationship of the 2005 AROE to Previous AROEs -- Importance of a Country Focus -- Overview of the 2005 AROE -- 2 Measuring and Managing Performance at the Country Level -- Strategic Planning -- Performance Measurement -- Performance Management -- Conclusions -- 3 Update on Monitoring and Evaluation of Bank Operations -- Monitoring of Bank Operations -- Evaluation -- Conclusions -- 4 Improving IEG's Effectiveness -- IEG's Response to 2004 AROE Recommendations -- IEG Client Survey Results -- Recommendation for IEG -- 5 Conclusions and Recommendations -- Recommendations -- Appendixes -- A: Review of CAS Results Matrices -- B: Country Director Survey Results on the Use of Monitoring and Evaluation Systems and Information at the Country Level -- C: Monitoring and Evaluation Framework in the Bank -- D: IEG Client Surveys -- E: Management Response -- Endnotes -- References -- Boxes -- 2.1 Elements of Results-Based Management -- 2.2 What Is a Results-Based CAS? -- 2.3 Harmonization Around Results -- 2.4 Observations from IEG's Review of the Poverty Reduction Strategy Initiative -- 2.5 IEG Lessons on Harmonization from Evaluation -- 2.6 Developing the Capacity to Manage by Results at the Country Level -- 2.7 How Performance Information Is Used -- 2.8 Incorporating Results in Portfolio Reviews -- 3.1 Lessons on Results-Based Management in the U.S. Federal Government -- Figures -- 2.1 Distribution of Performance Measures by Evaluation Level.
Keywords: Electronic commerce; Financial literacy; Financial literacy